Social and labor legal relations in the coordinate system of the state security of the Republic of Kazakhstan - Mezhibovskaya И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article analyzes some problems of ensuring the national security of the Republic of Kazakhstan in the format of the implementation of the state social policy presented by the legislative regulator of labor law and social security law. It examines the issues of the concept of security, its types and levels. The article analyzes the difference in approaches to the concepts and content of national and state security in foreign countries, the distinctive features of the content and semantic interpretations presented by scientists of the near and far abroad countries. The analytical study is based on both national legal levers and the norms of international law that constitute the basic foundations of socioeconomic security, including those that create social threats and challenges. Special attention is paid to the issues of legal incidents presented today by the norms of the current legislation of the Republic of Kazakhstan in the context of their potential projections of threats to national security in Kazakhstan. The author reveals the aspects of the negative impact of certain norms of law on the process of formation of social national security of the Republic of Kazakhstan on the example of legal casuistry, building a study on the principle of increasing legal potential: from one legal norm presented in the article of the law "On children’s villages and youth homes" to the format of the entire legislative act - the law "On Social Protection of citizens affected by an environmental disaster in the Aral Sea region" and international treaties ratified by the Republic of Kazakhstan and having priority over the laws of the country, on the example of the status of migrant workers. The article analyzes interrelated, interdependent sets of complex legal processes for the legal regulation of certain social and labor relations, which, without taking into account national variability and interstate flexibility, actuarial forecasting, elementary illiteracy, lead to legal casuistry, the impossibility of the real functioning of legal attitudes and, ultimately, affect the elementary components of the security system of countries.